Exploring the concept of problematic khat use in the Gurage community, South Central Ethiopia: a qualitative study. Issue 10 (12th October 2020) - Mihretu, Awoke; Fekadu, Abebaw; Habtamu, Kassahun; Nhunzvi, Clement; Norton, Sam; Teferra, Solomon
Abstract : Objective: This study aimed to explore how problematic khat use is characterised in the Gurage community in South Central Ethiopia. Design: Qualitative study. Setting: Gurage community in South Central Ethiopia. Participants: We conducted indepth interviews with 14 khat users and 5 non-khat users, and three focus group discussions with khat users. Methods: All participants were selected purposively based on their exposure to khat or khat use. We used an interview guide to explore the perceptions of participants about khat use and problematic khat use. We analysed the data thematically using OpenCode V.4.03 software. We used iterative data collection and analysis, triangulation of methods, and respondent validation to ensure scientific rigour. Findings: We identified three major themes: sociocultural khat use, khat suse (khat addiction) and negative consequences of khat use. Sociocultural khat use included a broad range of contexts and patterns, including use of khat for functional, social, cultural and religious reasons. Khat addiction was mainly explained in terms of associated khat withdrawal experiences, including harara/craving and inability to quit. We identified mental health, sexual life, physical health, social and financial negative consequences of khat use. The local idiom jezba was used to label a subgroup of individuals with khat suse (khat addiction). Conclusion: The study has identified what constitutes normative and problematic khat use in the Gurage community in South Central Ethiopia. Problematic khat use is a broad concept which includes frequency, reasons, contexts, negative consequences and addiction to khat. Insights generated can be used to inform future studies on the development of tools to measure problematic khat use.